THE EFFECT OF THIN CAPITALIZATION RULE TO CORPORATE CAPITAL STRUCTURE IN INDONESIA - Ramadhan, Muhammad Rheza; Riandoko, Riko . (FEB Universitas Sam Ratulangi Manado, 2017)
This research finds the effect of thin capitalization rule implementation to corporate capital structure (debt and equity) in Indonesia. This study used leverage data in 2015 (before the implementation) and 2016 (after the implementation). The data was seperated with the leverage above 4:1 and below 4:1. The data was processed using paired sample t-test. Based on hand-collected sample of 76 publicity- listed indonesian firms for the 2015 and 2016 year, we found that the thin capitalization rule significantly affected corporate capital in both the sample with Debt to Equity Ratio above 4:1 and Debt to Equity Ratio below 4:1 and doesnâ€™t significantly affected corporate debt in both the sample with Debt to Equity Ratio above 4:1 and Debt to Equity Ratio below 4:1.Â